2017
DOI: 10.1007/s00228-017-2220-8
|View full text |Cite
|
Sign up to set email alerts
|

Number of medications and adverse drug events by unintentional poisoning among older adults in consideration of inappropriate drug use: a Swedish population-based matched case-control study

Abstract: PurposeThis national, population-based study aims to determine the association between the number of prescribed medications and adverse drug events (ADE) by unintentional poisoning and examine this risk when known indicators of inappropriate drug use (IDU) are accounted for.MethodsWe employed a matched case-control design among people living in Sweden who were 50 years and older. Cases experiencing an ADE by unintentional poisoning resulting in hospitalization or death (n = 5336) were extracted from the Nation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 36 publications
0
17
0
Order By: Relevance
“…The identification of such distinct subgroups could be used to help target therapies and trials in heterogeneous syndromes such as ACHD. Clinical trials are prone to select patients without marked comorbidity, but concurrent use of different drugs is important to identify due to increased risk of drug–drug interactions and ADEs 26 , 27 . This may be most crucial in the comorbidity subgroup.…”
Section: Discussionmentioning
confidence: 99%
“…The identification of such distinct subgroups could be used to help target therapies and trials in heterogeneous syndromes such as ACHD. Clinical trials are prone to select patients without marked comorbidity, but concurrent use of different drugs is important to identify due to increased risk of drug–drug interactions and ADEs 26 , 27 . This may be most crucial in the comorbidity subgroup.…”
Section: Discussionmentioning
confidence: 99%
“…However, another study is now investigating the reduction of inappropriate medication in multimorbid patients (Hasler et al 2015). A recent Swedish study by Rausch et al (2017) reported the total number of used drugs and inappropriate medication as associated with hospitalizations for unintentional poisoning.…”
Section: Discussionmentioning
confidence: 99%
“…However, this definition encompasses vast swathes of the population: 50% of Medicare beneficiaries receive five or more medications (31), as do 84% of older adults with cancer, 43% receive 10 medications or more (32). In my view, cutoff numbers should not be the main concern, since IMUP can occur with even a single medication and the risk of IMUP increases in a direct relationship with the number of medications prescribed (30,(33)(34)(35)(36). Given its futile nature, the time has come to close the door on the debate surrounding the definition of IMUP, and move the discourse decisively towards its effective treatment.…”
Section: Defining Imup: a Futile Debatementioning
confidence: 99%